The Difficulties Semi-Linear in Low dimensions between Brezis and Nirenberg - Dr. BUSHARA EISA HAMAD ABDALLA (White Nile Journal for Studies and Research, 2025)
This study discusses existence results for a quasi-linear elliptic equation of critical Sobolev growth [ ] in the low-dimensional case, where the problem has a global character which is encoded in sign properties of the “regular” part for the corresponding Green’s function as in [ ]. Keywords: Brezis- Nirenberg problem, Low dimensions, (1+ -Laplace operator, Blow up.